Sankara Nethralaya's manual of medical laboratory techniques - Ramakrishnan, S.; Sulochana, K. N. (Jaypee Brothers Medical Publishers (P) LTD, 2012)
This manual is a complete guide to medical laboratory techniques used in medical microbiology, haematology, clinical biochemistry, histopathology, human genetics and molecular biology. With the help of detailed images and illustrations, the authors discuss common tests such as blood glucose estimation and simple microscopy, as well as more sophisticated tests such as high performance liquid chromatography. For each test, the principles, methods, results, norms and interpretations are described.